Generalized derivations on Lie ideals of completely semiprime ? -rings - Rahman, MM; Paul, AC (Bangladesh Journal of Scientific Research, 2016)
In this paper we prove that under some suitable conditions, every Jordan generalized derivation on Lie ideals of a 2-torsion free completely semiprime ? -ring is a generalized derivation on the same. Bangladesh J. Sci. Res. 27(1): 87-98, June-2014